The Effect of STAD Cooperative Learning on Mathematical Representation Ability and Student Interests - Sriwahyuni Fitrianita Purba (JMEA : Journal of Mathematics Education and Application, 2022)
Preliminary studies display that students' representational abilities and interest in mastering are nevertheless low. One manner to enhance its miles through implementing STAD kind cooperative mastering. This look at objectives to decide: (1) the impact of STAD type cooperative mastering on college students' mathematical illustration skills. (2) The effect of STAD type cooperative gaining knowledge of on college students' hobby in getting to know. The research approach used is experimental research within the application of cooperative studying kind (STAD) inside the experimental magnificence and traditional learning in the control magnificence. The population on this observe consisted of all students of class XI SMA Negeri 1 Labuhan Deli totaling 219 students. The pattern in this take a look at consisted of the experimental magnificence XI MIA2 and the manipulate magnificence XI MIA1, each of which amounted to 32 people. The prerequisite test become achieved with normality test using Kolmogorov Smirnov take a look at, homogeneity take a look at using Lavene statistical check. Speculation checking out turned into accomplished the use of way Anova evaluation with a significance level of 5%. The consequences showed that: (1) there was an effect of STAD kind cooperative getting to know on the students' mathematical illustration capability of 28.5%; (2) there has been an effect of cooperative mastering kind STAD on college students' interest in studying with the aid of 28.8%. Consequently, it could be concluded that the application of STAD is capable of boom the ability and interest of representatives in pupil mastering.